The Transformative Elements of Tourism Related Service Concepts A Finnish Context - Sofroneeva, Ekaterina (My University, 2017)
Our society is already evolving into the ―transformational economy‖ where transformation of individuals for a new image according to their dreams is the new economic offering. Transformational economy within the service is located in the emerging new research trend: transformative service research (TSR). TSR examines aspects such as the social and ecological consequences, the impact of services on well-being and sustainability. The research issue is that there is a lack in research on transformational service concepts in Finland. This research aims to identify transformational tourism services in Finland. The primary objective of this study is to identify the transformational tourism elements that Finnish tourism companies apply. There are three key theoretical areas that this thesis examines to provide a solid picture of the different types of transformational tourism in Finland. Firstly, this study focuses on the concept of transformational tourism through literature review, and secondly aims to understand the nature of the transformative learning, particularly in tourism sector. Thirdly, the new service development concepts are discussed and adapted. The literature part of this thesis systematically examines published articles in books and journals regarding these three key theoretical areas. To further extent and in support of the picture, the thesis discusses findings of a qualitative empirical study from the Finnish tourism industry by using semi-structured interviews with managers of the companies. The findings of the study suggest that there are 6 different transformational elements (TTE) applied by the Finnish tourism companies. In particular, the six types of TTE used in different levels by different companies. The description of each company configuration is available under the synthesis section.
Keywords: Transformative elements; Transformational tourism; Transformational learning; TSR; New service development; Tourism Industry; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|